TOTAL BACTERIA, COLIFORMS AND NON-COLIFORMS IN THE MILK OF ETAWA CROSSBREED IN SINGAPADU KALER VILLAGE, SUKAWATI DISTRICT, GIANYAR REGENCY - Katharina Diena Bhoki; I Nengah Kerta Besung; I Gusti Ketut Suarjana (Buletin Veteriner Udayana, 2024)
Etawa crossbreed goat's milk is a source of animal protein that is increasingly in demand by the public because it has very high nutritional value. Besides its nutritional value, milk is also a good medium for the growth of various types of microorganisms. This study aims to determine the total bacteria, coliforms and non-coliforms in Etawa crossbreed goat milk. The data taken is milk from the entire population of Etawa crossbreed goats that are currently lactating. This research is a type of observational research with a purposive sampling method. Counting total bacteria, coliforms and non-coliforms using the spread plate technique. The data obtained were analyzed descriptively by counting the number of bacteria in the culture media. The results showed that the total bacteria average was 3 x 10⁶ ± 1 x 10⁶ cfu/ml, coliforms were 2 x 10³ ± 1 x 10³ cfu/ml and non-coliforms were 2.2 x 10⁶ ± 2.5 x 10⁶ cfu/ml. Based on the research results, it can be concluded that the microbial contamination limit does not meet SNI. It is necessary to improve the cleanliness of cages and livestock so that bacterial contamination in milk can be reduced and further tests need to be carried out on the types of pathogenic and zoonotic bacteria present in the milk of Etawa crossbreed goats in Singapadu Kaler Village, Sukawati District, Gianyar Regency